The Case: A Son’s Request to Forgo Treatment - Mishra, Ruchika (Cambridge quarterly of healthcare ethics, 2014)
To submit a case that has been reviewed by an ethics committee or to submit papers on related topics in clinical ethics, readers are invited to contact section editor Ruchika Mishra at ruchika.mishragmail.com.